Long non-coding RNA MIR22HG impedes the progression of anaplastic thyroid carcinoma via targeting miR-141-3p/PTEN/AKT axis - Junyu Cao; Peng Jiang; Songliang Jiang; Yuhan Zhao; Xin Jiang; Chuancheng Zhou; Jing Li; Kunxian Yang (Endokrynologia Polska)
INTRODUCTION: Anaplastic thyroid carcinoma (ATC) is one of the most aggressive and lethal malignancies. The MiR-22 host gene (MIR22HG) has been identified as a novel long non-coding RNA (lncRNA) in a few types of cancer. Nevertheless, little is known about the potential role of MIR22HG in ATC. In this study, we aimed to investigate the biological functions and underlying molecular mechanisms of MIR22HG in ATC. MATERIAL AND METHODS: The expression of MIR22HG in tissues and cells of ATC were detected by quantitative real-time polymerase chain reaction (qRT-PCR). The cell viabilities and invasive abilities were evaluated by 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay, wound healing assay, and Matrigel invasion assay. The mechanism of MIR22HG interacting with microRNA-141-3p (miR-141-3p) was measured by RNA immunoprecipitation (RIP) assay, RNA pull-down assay, and dual-luciferase reporter assay. RESULTS: MIR22HG was downregulated in ATC tissues and cells. More importantly, decreased expression of MIR22HG was found to be correlated with poor prognosis of ATC patients. Functional analysis showed that overexpression of MIR22HG attenuated the proliferation and metastasis of ATC both in vitro and in vivo. Mechanistically, MIR22HG positively modulated phosphatase and tensin homolog deleted on chromosome ten (PTEN) expression via sponging miR-141-3p, thus inhibiting downstream protein kinase B (AKT) signaling cascade. CONCLUSIONS: MIR22HG serves as a tumor suppressor in ATC and impedes the progression of ATC through regulation of miR-141-3p/PTEN/AKT axis. Our findings illustrate the critical role of the MIR22HG/miR-141-3p/PTEN/AKT axis in the progression of ATC, which offers new insights for the therapeutic strategies of ATC.